2016
DOI: 10.1039/c6em00074f
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposures and DNA methylation in newborns: a pilot study in Durban, South Africa

Abstract: The in utero environment has the potential to influence epigenetic programming and subsequently the health of offspring. Even though pregnant women living in urban Africa are exposed to multiple chemicals and infectious agents that may impact their developing children, the neonatal epigenome has not been studied in these regions. We assessed whether prenatal exposures to air pollution and maternal human immunodeficiency virus (HIV) are associated with changes to DNA methylation throughout the epigenome using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…To understand whether in utero air pollution exposure affects DNAm, a number of studies have examined placenta or cord blood samples [33, 34, 41, 42]. One study showed a significant concentration-dependent association between exposure to NO 2 during pregnancy and DNAm at three CpGs in cord blood samples measured using the Illumina 450K platform (Table 1 and Additional file 2: Table S2) [41].…”
Section: Effects Of Air Pollutants On Dna Methylation Across the Lifementioning
confidence: 99%
See 1 more Smart Citation
“…To understand whether in utero air pollution exposure affects DNAm, a number of studies have examined placenta or cord blood samples [33, 34, 41, 42]. One study showed a significant concentration-dependent association between exposure to NO 2 during pregnancy and DNAm at three CpGs in cord blood samples measured using the Illumina 450K platform (Table 1 and Additional file 2: Table S2) [41].…”
Section: Effects Of Air Pollutants On Dna Methylation Across the Lifementioning
confidence: 99%
“…An alternative to an epidemiological study approach is to compare people living in areas with different air pollution concentrations, for example, an area with lots of industry and high air pollution with a rural area nearby with low air pollution [27, 3234]. After correction for differences between the populations living in these two locations, comparison allows estimation of the effects of the increased air pollution exposure associated with living in the industrial area.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is the most frequent chronic disease in children [ 1 ], and its prevalence continues to increase, raising global public health concerns [ 2 4 ]. Previous studies found that high prenatal ambient air pollutant (AAP) exposure alters epigenetic programming in utero [ 5 ] and that children are at greater risk of developing asthma when exposed to higher concentrations of AAPs [ 6 ]. This further raises concern and increases the urgency of understanding the relationship between AAP exposures and asthma and finding effective ways to prevent, treat, and/or cure asthma.…”
Section: Introductionmentioning
confidence: 99%
“…These markers were often able to distinguish traffic-exposed individuals from controls but only one of the 63 papers from this review was from an African-based study (DeMarini, 2013). Prenatal exposure to air pollution and HIV status of mothers appeared to lead to differential methylation in infants particularly in certain biological pathways related to metabolic processes and viral regulation (Goodrich et al, 2016). Only one study evaluated epigenome-wide DNA methylation and this study found differential methylation in genes related to growth and immune function for infants of aflatoxin-exposed mothers (Hernandez-Vargas et al, 2015).…”
Section: G X E and Related Integration Of Genomic And Environmental Ementioning
confidence: 96%
“…Additional outcomes evaluated included markers of oxidative stress, inflammatory cytokines, and chemokines (Cachon et al, 2014), chronic bronchitis from occupational exposures to dust (Hinson et al, 2016), elevated prostate specific antigen (PSA) among young men exposed occupationally to quarry pollutants (Ewenighi et al, 2017), chronic respiratory symptoms among limestone factory workers in Zambia (Bwalya et al, 2011), and allergic rhinitis in urban areas (Flatin et al, 2018). Exacerbation of silicosis due to higher doses of particulate matter exposure, impacts of exposure to prenatal air pollution on DNA methylation in the context of HIV status and antiretroviral treatment (Goodrich et al, 2016), asthma and asthma exacerbations, mortality, cerebrovascular outcomes, cardiovascular outcomes, and daily respiratory mortality were also evaluated.…”
Section: Health Outcomesmentioning
confidence: 99%